Bacteriological and Epidemiological Characteristics of Enterotoxigenic Escherichia coli Isolated in Tokyo, Japan, between 1966 and 2009 - Konishi, Noriko (American Society for Microbiology, 2011)

(untitled)
Enterotoxigenic Escherichia coli (ETEC) caused 131 outbreaks in Tokyo, Japan, between 1966 and 2009. The major serogroups were O6, O27, O148, and O159. The incidence of serogroups O25 and O169 recently increased. Heat-stable enterotoxin (ST) subtyping revealed that E. coli of serogroups O6, O15, O25, and O159 possessed the STh gene, whereas those serotyped as O27 and O169 possessed the STp gene.